Role of Diabetic Dyslipidemia on Coronary Atherosclerotic Severity in Acute Coronary Syndrome - Rabbani, Golam Mahfuz; Rahman, Afzalur; Khan, Anisur Rahman; Hossain, Nur; Alam, Muhammad Badrul; Khan, Amiruzzaman; Asaduzzaman, Khondoker (Bangladesh Heart Journal, 2017)
Aims: To evaluate the association of coronary atherosclerotic severity in diabetic dyslipidemic patients of acute coronary syndrome. Methods: This was a cross sectional comparative analytical study, done in the Department of Cardiology, Sir Salimullah Medical College Mitford Hospital and Ibrahim Cardiac Hospital & Research Institute, Dhaka, during September 2009 to August 2010. Results: Most of the patients (57.5%) were in the age range of 40-70 years. Atherosclerotic severity in diabetic ACS patients was significantly higher with low HDL, high TC/HDL and high LDL/HDL ratio. Low HDL, high TC/HDL and high LDL/HDL ratio are indicators of the extent and severity of coronary artery disease. More frequent dyslipidemia in diabetic ACS patients were low HDL and it was about 54%. Conclusion: Atherosclerotic severity in diabetic acute coronary syndrome patients was significantly more in dyslipidemic group than non dyslipidemic group. Bangladesh Heart Journal 2016; 31(2) : 65-69